The influence of APOE and TOMM40 polymorphisms on hippocampal volume and episodic memory in old age - Ferencz, Beata; Laukka, Erika J.; Lövdén, Martin; Kalpouzos, Grégoria; Keller, Lina; Graff, Caroline; Wahlund, Lars-Olof; Fratiglioni, Laura; Bäckman, Lars (Frontiers in Human Neuroscience, 2013)
Mitochondrial dysfunction is implicated in neurodegenerative disorders, such as Alzheimer’s disease. Translocase of outer mitochondrial membrane 40 (TOMM40) may be influential in this regard by influencing mitochondrial neurotoxicity. Little is known about the influence of the TOMM40 gene on hippocampal (HC) volume and episodic memory (EM), particularly in healthy older adults. Thus, we sought to discern the influence of TOMM40 single nucleotide polymorphisms (SNPs), which have previously been associated with medial temporal lobe integrity (rs11556505 and rs2075650), on HC volume and EM. The study sample consisted of individuals from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K) who were free of dementia and known neurological disorders, and 60-87 years of age (n = 424). EM was measured by using a 16-item word list with a 2-minute free recall period and delineation of the HC was performed manually. The influence of Apolipoprotein E (APOE) and TOMM40 was assessed by 2x2 ANOVAs and partial correlations. There was no effect of APOE and TOMM40 on EM performance and HC volume. However, partial correlations revealed that HC volume was positively associated with free recall performance (r=0.21, p<0.01, r2 =0.04). When further stratified for TOMM40, the observed association between HC volume and free recall in APOE ε4 carriers was present in combination with TOMM40 rs11556505 any T (r=0.28, p<0.01, R2 =0.08) and rs2075650 any G (r=0.28, p<0.01, R2 =0.08) “risk” alleles. This pattern might reflect higher reliance on HC volume for adequate EM performance among APOE ε4 carriers with additional TOMM40 “risk” alleles suggesting that the TOMM40 gene cannot merely be considered a marker of APOE genotype. Nevertheless, neither APOE nor TOMM40 influenced HC volume or EM in this population-based sample of cognitively intact individuals over the age of 60.